The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.cdd.4401427
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of protein carbonylation in the apoptotic response to oxidative stress associated with photodynamic therapy: a cell biochemical and proteomic investigation

Abstract: We previously reported that photodynamic therapy (PDT) using Purpurin-18 (Pu-18) induces apoptosis in HL60 cells. Using flow cytometry, two-dimensional electrophoresis coupled with immunodetection of carbonylated proteins and mass spectrometry, we now show that PDT-induced apoptosis is associated with increased reactive oxygen species generation, glutathione depletion, changes in mitochondrial transmembrane potential, simultaneous downregulation of mitofilin and carbonylation of specific proteins: glucoseregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 58 publications
11
87
0
4
Order By: Relevance
“…Further, deletion of the miR494-containing chromosomal fragment frequently occurs in different cancers [59] and, interestingly, restoring miR494 levels in renal carcinoma cells promotes cellular apoptosis in a process requiring Drp1-dependent mitochondrial fragmentation [60,61]. In addition, anticancer drug treatments have been shown to downregulate the activity of different MICOS proteins, thus affecting the cristae shape and presumably inducing oxidative stress [62,63], although the potential involvement of mitochondrial dynamics has been not investigated in these cases. On the contrary, it has been recently demonstrated that during apoptosis the ATP synthase Inhibitory Factor 1 (IF1), which prevents dissipation of ATP levels due to a reversal activity of ATP synthase, is also able to inhibit Oma-1-dependent Opa-1 processing, thus preventing the cristae remodelling and cytocrome-c release [64].…”
Section: Mitochondria-shaping Proteins In Apoptosismentioning
confidence: 99%
“…Further, deletion of the miR494-containing chromosomal fragment frequently occurs in different cancers [59] and, interestingly, restoring miR494 levels in renal carcinoma cells promotes cellular apoptosis in a process requiring Drp1-dependent mitochondrial fragmentation [60,61]. In addition, anticancer drug treatments have been shown to downregulate the activity of different MICOS proteins, thus affecting the cristae shape and presumably inducing oxidative stress [62,63], although the potential involvement of mitochondrial dynamics has been not investigated in these cases. On the contrary, it has been recently demonstrated that during apoptosis the ATP synthase Inhibitory Factor 1 (IF1), which prevents dissipation of ATP levels due to a reversal activity of ATP synthase, is also able to inhibit Oma-1-dependent Opa-1 processing, thus preventing the cristae remodelling and cytocrome-c release [64].…”
Section: Mitochondria-shaping Proteins In Apoptosismentioning
confidence: 99%
“…Most often, the proteomics studies aiming at the identification of oxidatively modified proteins also take into account the increase or decrease in protein amounts (e.g. [40,42]). However, some studies focus only on protein amount changes, regardless of any modification-specific study, in biological situations where oxidative stress is suspected.…”
Section: Cell Biology Proteomics Studies Related To Oxidative Stressmentioning
confidence: 99%
“…Enhanced capability to overcome oxidative protein carbonylation may be means of cancer cells to produce prosurvival in oxidative stress environment. This is because carbonylation of proteins in cells such as glucose-regulated protein-78, heat-shock protein 60, heatshock protein cognate 71, phosphate disulphide isomerase, calreticulin, beta-actin, tubulin-alpha-1-chain and enolase-alpha trigger the apoptosis of cells (Magi et al 2004). Further analysis to validate these hypotheses were not performed in this study due to limitation of funds.…”
Section: Discussionmentioning
confidence: 97%